Forecasting COVID-19 recovered cases with Artificial Neural Networks to enable designing an effective blood supply chain - Ayyildiz, Ertugrul; Erdogan, Melike; Taskin, Alev (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
This study introduces a forecasting model to help design an effective blood supply chain mechanism for tackling the COVID-19 pandemic. In doing so, first, the number of people recovered from COVID-19 is forecasted using the Artificial Neural Networks (ANNs) to determine potential donors for convalescent (immune) plasma (CIP) treatment of COVID-19. This is performed explicitly to show the applicability of ANNs in forecasting the daily number of patients recovered from COVID-19. Second, the ANNs-based approach is further applied to the data from Italy to confirm its robustness in other geographical contexts. Finally, to evaluate its forecasting accuracy, the proposed Multi-Layer Perceptron (MLP) approach is compared with other traditional models, including Autoregressive Integrated Moving Average (ARIMA), Long Short-term Memory (LSTM), and Nonlinear Autoregressive Network with Exogenous Inputs (NARX). Compared to the ARIMA, LSTM, and NARX, the MLP-based model is found to perform better in forecasting the number of people recovered from COVID-19. Overall, the findings suggest that the proposed model is robust and can be widely applied in other parts of the world in forecasting the patients recovered from COVID-19.
Keywords: Artificial neural networks; CIP Therapy; COVID-19; Forecasting; Blood supply chain; CORRELATION-COEFFICIENT; TIME-SERIES; PREDICTION; DEMAND; OUTBREAK; ARIMA; PREVALENCE; PERCEPTRON; ROOT; FUEL; Life Sciences & Biomedicine - Other Topics; Computer Science; Engineering; Mathematical & Computational Biology